Multilevel switching in Mg-doped HfOx memristor through the mutual-ion effect - Li, Li-Heng; Xue, Kan-Hao; Zou, Lan-Qing; Yuan, Jun-Hui; Sun, Huajun; Miao, Xiangshui (Applied physics letters, 2021)
HfOx memristor is one of the most promising candidates for nonvolatile memory and neuromorphic computing applications, but for the latter, its gradual conduction modulation and switching linearity still need improvement. In this work, uniform and multilevel resistance switching (RS) of HfOx memristors have been achieved through Mg doping, which is a distinct dopant other than previously used elements like Al and Gd. Moreover, the Mg-doped HfOx memristor exhibits excellent continuous conductance modulation characteristics under pulse voltage. First-principles calculations and conductive mechanism analysis show that Mg can migrate into the conductive filaments (CFs) by adjusting oxygen vacancy migration and defect states in the CFs, resulting in the improved RS performance of HfOx memristors. The reason why Mg doping rather than Ca doping could yield improved RS performances is clarified. Our work shows the unique functionality of Mg dopants in HfOx and provides a feasible way to improve RS performance of transition metal oxide memristors and its guiding principles.